CO2 Adhesion Characteristics on Solid Surfaces under CO2 Geologic Sequestration Environment. (25th February 2022) - Sun, Jingyue; Xu, Haopo; Chen, Cong; Li, Tonglai; Li, Weizhong; Qin, Yan
Abstract : Wettability at mineral-CO2 interface in CGS (carbon geosequestration) is a key parameter for risk assessments and storage capacity estimations. Many studies of wettability achieved inconsistent results, while adhesion could be a potential mechanism causing huge wettability alteration. CO2 adhesion characteristics have been revealed for CO2 /brine/mica system under a wide range of pressures, temperatures, and salinities by analyzing static and dynamic contact angles. Under all experiment conditions, the average static CA ranges from 19.5° to 32.1°. In 8 MPa experiments, CA decreases from 26.0° to 19.5° with the increasing salinity. Similar trends were also observed under 12 MPa condition. However, CA does not show clear dependence on pressure. A concentric probe was designed by which vertical position of the probe can be changed by rotating the screw of the probe holder while horizontal degrees of freedom are restricted. With this concentric probe, contact angles were obtained at different positions of the same sample to investigate the effect of heterogeneity of sample surface. Uncertainty and large hysteresis of dynamic contact angles were found which related with measurement positions. These large hystereses as obvious sign of adhesion had good repeatability at specific surface positions. Further electron microscope test demonstrated the correlation between large hysteresis and smoother surfaces which is consistent with the DLVO theory-based water film thickness hypothesis on adhesion. This study enriched the data on the wettability of mica and may shed light on CO2 adhesion on solid surfaces for better understanding the fate of CO2 during sequestration.